FRINGE BENEFIT AND JOB SATISFACTION IN SME: AN EMPIRICAL EXPERIENCE AMONG SMES IN SELANGOR - Zulkiflee Abd Rahim @ Ab Rasim; Amirul Syafiq Mohd Ghazali; Halimi Poniran; Mohd Reza Abdol Ghani; Abu Dzarr Muhhamad Rus; Mohd Zool Khazani Zainal (Journal of Islamic, Social, Economics and Development, 2021)
This study is aimed to investigate the relationship between fringe benefit and job satisfaction among SME workers in Selangor. Data were collected from 200 workers with various backgrounds by distributing questionnaires using a convenient sampling approach. The collected data of 200 were analysed by using the PLS-SEM. The findings indicate a positive correlation between fringe benefit and job satisfaction in SME’s employees. Health and insurance, allowance, bonus and reward contribute to the job satisfaction among SME’s employees.